151 Improving diagnosis and care in progressive supranuclear palsy (PSP), corticobasal degeneration (CBD). Issue 12 (14th November 2019) - Swallow, Diane; Grosset, Donald; Counsell, Carl
Abstract : Background: Misdiagnosis and delayed diagnosis are common in PSP/CBD. After diagnosis there is little evidence on multidisciplinary care access or on prognosis other than survival. Aims: (1) Describe and improve diagnostic pathways; (2) Validate and develop diagnostic tools; (3) Evaluate care quality from diagnosis to end-of-life; (4) Evaluate patient and carer prognosis; (5) Evaluate activity limitations as measures of disease progression and outcomes for clinical trials. Methods: Individuals with PSP/CBD are recruited nationally across Scotland. Patients consent to medical record access, data linkage, clinical examination and questionnaires covering multiple domains, postal follow-up and MRI. Each PSP/CBD patient nominates a carer to return questionnaires about their health, carer burden and proxy assessments of their relative's capabilities. PD controls undergo motor/cognitive examination and MRI. Results: 73 PSP/CBD patients, 63 carers and 26 age-sex matched PD controls have been recruited to date. 69(94.5%) PSP/CBD cases have consented to longitudinal clinical assessment, medical record review and data linkage, and 4(5.5%) to medical record/data linkage only. 56(76.7%) have consented to longitudinal MRI. Anticipated outcomes: Understanding the causes of delayed diagnosis and the assessment of new diagnostic tools will facilitate improved diagnosis. A better understanding of patient and carer prognosis will improve care planning and provision.